Cytological findings of NK/T-cell lymphoma in pericardial effusion: A case report with a review of the literature - Yeeun Han; Kyung Ha Kim; In Ho Choi (Wolters Kluwer Medknow Publications, 2019)
Extranodal Natural Killer/T-cell lymphoma (ENKL) is an aggressive NK or cytotoxic T-cell neoplasm. The cytological features of NK/T-cell lymphoma have been rarely described, mainly focusing on the fine needle aspiration cytology from lymph nodes or soft tissue, except for a few cases focused on body fluid. A 46-year-old man visited the hospital due to generalized weakness and weight loss. Three months prior, computed tomographic scan revealed mesenteric panniculitis and reactive lymph nodal enlargement, as well as a mildly thickened left adrenal gland, suggesting an inflammatory condition. About 100 days later, marked enlargement of both adrenal glands with pericardial effusion was noted. The pericardial effusion contained medium-sized atypical lymphocytes, suspicious for malignant lymphoma, and the left adrenal mass was histologically confirmed as ENKL on biopsied specimen. Herein, we describe the cytological features of NK/T-cell lymphoma in body fluid cytology along with a review of the literature.